Systematic review of the health and societal effects of medication organisation devices. Issue 1 (December 2016) - Watson, Steven; Aldus, Clare; Bond, Christine; Bhattacharya, Debi
Abstract Background Suboptimal medication adherence is a significant threat to public health and resources. Devices that organise weekly doses by time and day are commonly used to reduce unintentional non-adherence. However, there is limited evidence to support their use. This systematic review was conducted to evaluate current evidence for their efficacy, safety and costs. Methods A pre-defined search of electronic databases from inception to January 2013 augmented with hand-searching was conducted. No limits were placed on publication date. Studies that compared organisation devices used by patients administering their own medication with standard medication packaging regardless of study design were eligible for inclusion. Studies that solely explored dispensing aspects of organisation devices were included whether or not they compared this to standard care. Screening of articles for inclusion and data extraction were completed independently by two reviewers with disagreements resolved by discussion. Outcomes were categorised into impact on health, medication adherence, healthcare utilisation, dispensing errors, supply procedures and costs. Risk of bias was also assessed. Results Seventeen studies met the inclusion criteria. Health outcomes were investigated in seven studies of which three reported a positive effect associated with organisation devices. Medication adherence was reported in eight studies of which three reported a positive effect. Three studies reported health care utilisation data but overall results are inconclusive. No optimal dispensing or supply procedures were identified. Economic assessment of the impact of organisation devices is lacking. All studies were subject to a high risk of bias. Conclusions Evidence regarding the effects of medication organisation devices was limited, and the available evidence was susceptible to a high risk of bias. Organisation devices may help unintentional medication non-adherence and could improve health outcomes. There is a strong need for more studies that explore the impact of such devices on patients, and an equally pressing need for studies that explore the impacts on healthcare services. Trial registration This systematic review is registered with PROSPERO (Registration numberCRD42011001718 ).